Intercellular DNA transfer mediated by migrasomes propagates genome instability - Li, Yi; Tang, Yihan; Ye, Guojun; Liu, Chunzhuo; He, Yide; Song, Chunyu; Chang, Weiping; Huang, Yuwei; Ji, Wei-ke; Deng, Lin (浪淘沙预印本平台, 2025)
Genome instability drives tumor evolution through incremental mutations and catastrophic events such as chromothripsis. Despite significant advances, the diversity and underlying mechanisms of genome instability remain insufficiently understood. Here, we identify a previously unrecognized form of genome instability termed "chromocytosis", in which chromosome bridge breakage during mitosis causes permanent loss of chromatin fragments from daughter cells. These extracellular fragments could be transferred into neighboring cells via migrasomes and compromise the genome integrity of the recipient cells. This intercellular chromatin transfer is conserved across cell types and observed in vivo in mouse tumor models and multiple human cancers. Disruption of migrasome formation attenuates chromocytosis and its genomic consequences. Our work establishes chromocytosis, the migrasome-mediated intercellular transfer of chromatin fragments, as a potent mechanism for propagating genomic instability and driving tumor evolution.